An Improved Design of Flat Panel Detector with Phototransistor PH101 Analysis of The Tube Voltage Setting - Nina Havilda; Muhammad Ridha Mak'ruf; Tri Bowo Indrato; Sedigheh Asghari Baighout (Jurnal Teknokes, 2022)
The intensity and quality of the X-Rays a patient receives is determined by the exposure factor. Voltage (kV), Current (mA), Time (seconds), and tube-to-film distance (FFD) are exposure factors that can be controlled and determined. The key factor that can determine the quality of X-Rays is the tube voltage (kV) which affects the X-Rays to penetrate objects. The purpose of this research is to improve image quality and relatively affordable manufacturing costs by obtaining the difference in the detector catch value between dark and light by utilizing the response of the PH101 phototransistor sensor. The contribution of this research is that the system can display grayscale and numeric on a 16x16 pixel matrix using the Matrix Laboratory (MATLAB) application. This research can convert images taken from analog data after measuring the phototransistor PH101 on X-Rays. The measurement settings used are 50, 55, 60, and 70kV, with a tube current of 40 mA and an irradiation time of 1 second. The measurement results show that the Flat Panel Detector Design can respond to differences in doses and objects. This research shows that a Flat Panel Detector and a Phototransistor PH101 sensor have been successfully made which can be used to capture X-Rays so that the black level of the film can be determined.